2021
DOI: 10.1093/jhered/esab050
|View full text |Cite
|
Sign up to set email alerts
|

Seascape Genetics of the Atlantic Spotted Dolphin (Stenella frontalis) Based on Mitochondrial DNA

Abstract: The Atlantic spotted dolphin (Stenella frontalis) is endemic to tropical, subtropical, and warm temperate waters of the Atlantic Ocean. Throughout its distribution, both geographic distance and environmental variation may contribute to population structure of the species. In this study we follow a seascape genetics approach to investigate population differentiation of Atlantic spotted dolphins based on a large worldwide dataset and the relationship with marine environmental variables. The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
2
1
0
Order By: Relevance
“…However, just three species dominated the sightings: bottlenose dolphins, pilot whales ( Globicephala macrorhynchus ) and spotted dolphins ( Stenella frontalis ) [ 53 ]. Comparing the results obtained here with these other two delphinid species, we observed the same lack of genetic structuring across the Canary Islands in spotted dolphins [ 54 ] but not in pilot whales [ 52 ]. On a broader scale, it has been described that spotted dolphins represent several distinct units in the Atlantic Ocean: Macaronesian group clustering, Canary Islands, Azores and Madeiran individuals [ 54 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, just three species dominated the sightings: bottlenose dolphins, pilot whales ( Globicephala macrorhynchus ) and spotted dolphins ( Stenella frontalis ) [ 53 ]. Comparing the results obtained here with these other two delphinid species, we observed the same lack of genetic structuring across the Canary Islands in spotted dolphins [ 54 ] but not in pilot whales [ 52 ]. On a broader scale, it has been described that spotted dolphins represent several distinct units in the Atlantic Ocean: Macaronesian group clustering, Canary Islands, Azores and Madeiran individuals [ 54 ].…”
Section: Discussionsupporting
confidence: 84%
“…The genetic differentiation observed between rough-toothed dolphins from the Caribbean and North Atlantic Ocean with Brazil-South Atlantic Ocean had been previously described (Donato et al, 2019;Silva et al, 2015), and agrees with other genetic studies with delphinids such as the Atlantic spotted dolphin Stenella frontalis (Cuvier, 1829) (do Amaral et al, 2021), bottlenose dolphin (Fruet et al, 2014), clymene dolphin Stenella clymene (Gray, 1850) (Nara et al, 2017), and common dolphin (Amaral et al, 2012), which reported a similar isolation pattern. Oceanographical features like the Amazon River mouth and the North Brazilian Current appear to act as a barrier that is segregating fauna from the northern and southern Brazil (Costa et al, 2017).…”
Section: Genetic Structure Of Panamanian and Caribbean Dolphins In Th...supporting
confidence: 90%
“…Southeastern Brazil did not show significant differentiation when compared to the Azores and Madeira. In a recent study that included a higher number of mtDNA sequences from both the Caribbean and from northeastern and southeastern Brazil as well as from Uruguay, population structure was found between a group of samples from oceanic origins: those from Azores, Madeira, the Canary Islands and the Mid-Atlantic Bight; those from the Caribbean and northeastern Brazil; and those from southeastern Brazil and Uruguay (do Amaral et al, 2021). Such population differentiation pattern could be explained due to isolation by distance, in which genetic distance can be correlated with the geographic distance between sample locations.…”
Section: Steno Bredanensismentioning
confidence: 99%